Neonatal abstinence syndrome: a never ending story! - Johannes N. van den Anker (Hygeia Press di Corridori Marinella, 2013)
Neonatal Abstinence syndrome (NAS) is the result of fetal exposure to illicit or prescription drugs (for example opioids, benzodiazepines, and selective serotonin reuptake inhibitors) taken by the mother prenatally. NAS is a complex of symptoms, caused by acute withdrawal of the illicit drug(s) used by their mothers during pregnancy, seen in neonates hours or days after being born. In the United States of America around 16% of teenagers and 7% of women between the ages of 18 and 25 use illicit drugs during their pregnancies. In this paper the treatment of opioid dependence during pregnancy and treatment of NAS are presented.   Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research